Perspective: Balance Assessments in Progressive Supranuclear Palsy: Lessons Learned - Dale, Marian L.; Prewitt, Austin L.; Harker, Graham R.; McBarron, Grace E.; Mancini, Martina (Frontiers in Neurology, 2022)
Many studies have examined aspects of balance in progressive supranuclear palsy (PSP), but guidance on the feasibility of standardized objective balance assessments and balance scales in PSP is lacking. Balance tests commonly used in Parkinson's disease often cannot be easily administered or translated to PSP. Here we briefly review methodology in prior studies of balance in PSP; then we focus on feasibility by presenting our experience with objective balance assessment in PSP-Richardson syndrome and PSP-parkinsonism during a crossover rTMS intervention trial. We highlight lessons learned, safety considerations, and future approaches for objective balance assessment in PSP.